Biological synthesis and characterization of silver nanoparticles synthesized from Pometia pinnata and Diospyros discolor Fruits. Issue 1 (February 2020) - Handayani, W; Nolia, I; Sundari, R M; Imawan, C
Abstract: The use of biological agents for nanoparticle biosynthesis is an alternative to the eco-friendly green synthetic method. In this study, fruit extracts from Pometia pinnata (Matoa) and Diospyros discolor (Bisbul) were used as reducing agents to produce silver nanoparticles (AgNPs). The ratio of silver precursors to water extracts from the fruit and the reaction time was observed to determine optimum reaction conditions. The characterizations were carried out using a UV-Vis spectrophotometer, Transmission Electron Microscope (TEM), and Particle Size Analyzer (PSA) to analyze the size and morphology of the AgNPs. With the increase in the volume ratio of extracts and silver nitrate, the absorption peak intensity tended to increase—these results were shown by the color of the colloid. Based on the comparison of these two extracts, the peak absorbance of the synthesis using D. discolor fruit extract was higher than P. pinnata . The result showed D. discolor fruit extracts had faster reaction times for AgNPs synthesis. The average size of silver nanoparticles from D. discolor was 32 nm and from P. pinnata was 51 nm. The use of D. discolor fruit extract tends to produce smaller AgNPs. This method can be developed for further application for antimicrobial nanoparticles and sensors.